Ferramenta gráfica para o dimensionamento de reservatórios para aproveitamento de águas pluviais: estudo de caso na região norte de Rondônia - Andrade, Vanessa Helena de (2017)
Rainwater harvesting systems have been pointed out as an important source to meet water demands. In general, the reservoir is the most expensive item of the system. Depending on the chosen method, the system can be over- or undersized. In addition, the region rainfall profile must be associated to the design of the tank. Therefore, this study aims to develop a graphical tool to assist rainwater harvesting tanks sizing, a case study in the region of Rondônia. It is proposed to draw a contour plot from the variables: catchment area, reservoir volume and efficiency in meeting domestic and industrial rainwater demands. The efficiency was obtained through the continuous water balance simulation method. Three surface fitting models were used to create the contour plot, Biharmonic spline interpolant, Locally weighted smoothing quadratic regression and Linear Polynomial, available on the MATLAB software. The influence region of the selected rainfall stations used for the continuous balance simulation was found by the Inverse Distance Weighting (IDW) method. Part of the northern region of Rondônia state was defined as graphic system influence area. In general, the surface fitting methods showed a good performance with R2 greater than 0,96. The Biharmonic spline interpolant method presented the best result due to its capability of explaining observed data variation. Hence, the generated contour plot can be used as decision-making aid tool in tank volume selection. Contour plots were developed to show the efficiency in meeting domestic and industrial rainwater demands as a function of a wide range of both catchment area and tank volume through the Biharmonic spline interpolant method. The RMSE values for validation were lower than 0,7. The residential demands to which surface fitting and contour graphics were developed vary between 60 and 600 L d-1; and the industrial demands vary between 500 and 50.000 L d-1.